一种地震储层预测方法 (2021)
本发明涉及一种地震储层预测方法。该地震储层预测方法：1)利用地震资料，对目标层地震构造进行解释，得到待预测区目标层地震层位解释数据；根据已完钻井的储层厚度、储层孔隙度数据，定义厚度加权平均孔隙度，计算储层评价系数；2)提取地震属性，并与储层评价系数进行回归分析，筛选出具有相关性的地震属性作为优选地震属性，建立优选地震属性与储层评价系数的相关关系；3)根据相关关系将优选地震属性网格转化为储层评价系数网格，再经校正处理，即得反映待预测区储层发育分布图。该方法建立储层评价系数与地震属性之间的关系，通过地震属性优化，实现了对储层的预测；该方法提高了储层预测的精度，满足了储层评价的需要。 The invention relates to an earthquake reservoir prediction method. The method comprises that 1) earthquake data is used to interpret earthquake construction of a target layer to obtain earthquake horizon interpretation data of the target layer in a to-be-predicted area, the thickness weighted average porosity is defined according to drilling finished reservoir thickness and reservoir porosity data, and an evaluation coefficient of a reservoir is calculated; 2) earthquake attributes are extracted, regression analysis is carried out on the reservoir evaluation coefficient and the earthquake attributes, an earthquake attribute with correlation is selected as a preferable earthquake attribute, and relation between the prefer